The Economic Impact of Kopi Gunung Kelir Geographical Indication on Farmer Groups in Semarang Regency - Sabbihisma Okta Tazkiya; Teguh Hardi Raharjo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Geographical Indications (GI) are promoted as instruments to enhance the competitiveness of region-based products and improve producers’ welfare; however, empirical evidence at the local community level in Indonesia remains limited and shows inconsistent economic outcomes. This study examines the impact of GI certification of Kopi Gunung Kelir on the economic conditions and governance of the farmers’ association (Gapoktan) in Semarang Regency. A qualitative narrative approach was employed through in-depth interviews, observation of production and quality control practices, and documentation of the GI book of requirements. Data were analyzed using condensation and narrative interpretation with source triangulation. The findings indicate that GI certification encouraged adjustments in production standards, strengthened quality control systems, and improved institutional coordination. Although product quality and market recognition increased, income improvement occurred gradually and was not evenly distributed. The results suggest that the economic effectiveness of GI depends on internal governance capacity and consistent implementation of standards at the community level.